2017
DOI: 10.3390/en10111862
|View full text |Cite
|
Sign up to set email alerts
|

Ice Cover Prediction of a Power Grid Transmission Line Based on Two-Stage Data Processing and Adaptive Support Vector Machine Optimized by Genetic Tabu Search

Abstract: Abstract:With the increase in energy demand, extreme climates have gained increasing attention. Ice disasters on transmission lines can cause gap discharge and icing flashover electrical failures, which can lead to mechanical failure of the tower, conductor, and insulators, causing significant harm to people's daily life and work. To address this challenge, an intelligent combinational model is proposed based on improved empirical mode decomposition and support vector machine for short-term forecasting of ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The group encountered difficulty in eliminating the mode mixing phenomenon at extremely small values of e , whereas, at an excessively large e , they observed that several extra IMF components are produced, leading to misjudgment of the results. The EEMD parameter settings for different application areas [40][41][42] refer to the method proposed by Wu and Huang [29]. In this study, the ensemble member M and the standard deviation of added white noise signal ' e of the EEMD were set to 100 and 0.2, respectively.…”
Section: Decomposing and Reconstructing Water Demand Time Seriesmentioning
confidence: 99%
“…The group encountered difficulty in eliminating the mode mixing phenomenon at extremely small values of e , whereas, at an excessively large e , they observed that several extra IMF components are produced, leading to misjudgment of the results. The EEMD parameter settings for different application areas [40][41][42] refer to the method proposed by Wu and Huang [29]. In this study, the ensemble member M and the standard deviation of added white noise signal ' e of the EEMD were set to 100 and 0.2, respectively.…”
Section: Decomposing and Reconstructing Water Demand Time Seriesmentioning
confidence: 99%
“…3. Machine learning models: [17][18][19][20][21][22][23][24] Liu et al 17 used a multivariate gray model to predict the shortterm ice-accretion thicknesses. To reduce the effects of cumulative errors from various micrometeorological factors on icing predictions, a model for predicting short-term icing on transmission lines was proposed in Huang et al, 18 based on a mixture of time-series analysis and the Kalman filter algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Although GSM can obtain the global optimal solution, that is, the optimal regression accuracy, it is usually conducted within the specified range. Once the search range is expanded, the algorithm training time will be very long [22][23][24]. To further improve the optimization performance and overcome the deficiencies of traditional algorithms, the Chinese scholar Sun Cheng-Yi et al raised the mind evolutionary algorithm (MEA) in 1998 [25].…”
Section: Introductionmentioning
confidence: 99%